The DMFS160: A new index for measuring post-radiation caries. (September 2020) - Watson, Erin; Eason, Brady; Kreher, Matthew; Glogauer, Michael
Abstract: The current systems used to measure post-radiation caries underestimate the severity of the disease by failing to account for the unique spread of post-radiation caries, including incisal-edge and cusp tip decay, enamel delamination and crown amputation. A novel and clinically applicable index to measure post-radiation caries is proposed. The DMFS160 index counts 5 surfaces per tooth, accounting for incisal-edge caries, and is broken down into missing surfaces and decayed/filled surfaces. A staging and grading system is used to capture enamel delamination and crown amputation. The staging and grading provides a clinically-relevant measure at the whole-mouth level and is paired with evidence-based treatment strategies. In this paper the DMFS160 index is applied to three cases and compared to the DMFS index, demonstrating the improved accuracy of the DMFS160 index in measuring the extent of post-radiation caries.